2004
DOI: 10.1108/00251740410513845
|View full text |Cite
|
Sign up to set email alerts
|

A matter of style: reconciling Henri and Henry

Abstract: During the twentieth century, much of the discussion about managerial behaviour centred on the difference between management functions and manager roles, with much of the debate centring on``Who is right, Mintzberg or Fayol?'' Reports on a study, involving 523 Australian managers, which suggests both are right ± Fayol gave us management as we would like it to be and Mintzberg gave us management as it is. In doing so, promulgates a set of new constructions of managerial behaviour ± preferred managerial style (m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
44
0
15

Year Published

2005
2005
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(62 citation statements)
references
References 25 publications
3
44
0
15
Order By: Relevance
“…Given the many definitions, in this work we use the words plan, organize, lead and control to describe the functions of the process approach. Detailed discussions concerning these functions are available in the works of Carroll and Gillen (1987), Koontz andO'Donnell (1978), andLamond (2004). Mintzberg (1973) was the leading author of the roles approach, also known as work activity school and belonging to the field of study of how managers spend their working hours (Stewart, 1967).…”
Section: Managers' Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the many definitions, in this work we use the words plan, organize, lead and control to describe the functions of the process approach. Detailed discussions concerning these functions are available in the works of Carroll and Gillen (1987), Koontz andO'Donnell (1978), andLamond (2004). Mintzberg (1973) was the leading author of the roles approach, also known as work activity school and belonging to the field of study of how managers spend their working hours (Stewart, 1967).…”
Section: Managers' Workmentioning
confidence: 99%
“…To make up the process approach section, we consulted the pioneering work of Mahoney, Jerdee, and Carroll (1965) about the categories of managers' work functions, and the questionnaire model used by Lamond (2004). Three questions were formulated for each of the four administrative functions, adding up to a total 12 questions, following the example presented in Figure 3.…”
Section: Organizational Life Cyclementioning
confidence: 99%
“…On the other hand, according to Parker and Ritson (2005) management scholars have always "known" Fayol and his links to F.W. Taylor, and so there has been no need to revisit the understanding of Fayol as a European adherent of scientific management (the falsity of this has been demonstrated by, among others, Lamond (2003Lamond ( , 2004). Was Fayol's approach to general and industrial administration simply a fad?…”
Section: Lenses On Management History: the Current Issuementioning
confidence: 99%
“…Rather, Mintzberg (1973Mintzberg ( , 1974 asserted, they enact a series of rolesinformational, decisional and symbolic -in various combinations according to the day-to-day exigencies they face. Lamond (2003Lamond ( , 2004 has sought to reconcile these apparently contradictory understandings by way of a comparison of managers' preferred approaches to managing with their experience of how they manage on a day-to-day basis. He concluded that the two views can be understood to be different layers of the same ontological reality, at least to the extent that, given the similarities between Fayol's characterisation and managers' preferences and between managers' day-to-day experiences and Mintzberg's roles, Fayol gave us management as we would like it to be and Mintzberg gave us management as it is.…”
Section: Lenses On Management History: the Current Issuementioning
confidence: 99%
See 1 more Smart Citation